Small Reviews (About the Event of Thought and the Crisis of Subject) - A. S. Robotova (Высшее образование в России)
The following text is a response to the publication of the journal in the rubric “Philosophy and history of science”. This text is called “Small Reviews”. Why? First of all, because the author has not set the task of a comprehensive analysis of publications. The text focuses on the pedagogical pragmatics of the peer-reviewed articles. In D.G. Ryndin’s article the author was attracted by that part, where the pedagogical practice of M.K. Mamardashvili was analyzed. Assessing the article of D.G. Ryndin as a whole positively, the reviewer believes that the author failed to convincingly show the poetics of philosophical speech and the fundamental relationship between the content and form of philosophizing and adduces her arguments for such an assessment. In the article devoted to the epistemological crisis of the subject, the reviewer has found many sources for pedagogical reflection and formulated them in the form of several provisions that should obviously be guided by each teacher. The reviewer believes that if the authors gave due consideration to the pedagogical theory and pedagogical characteristics of the subject, they would have enriched the their ideas about the crisis of education, its causes and consequences.